2008
DOI: 10.1124/jpet.108.145011
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Cannabinoid CB2Receptor-Selective Agonist, A-836339 [2,2,3,3-Tetramethyl-cyclopropanecarboxylic Acid [3-(2-Methoxy-ethyl)-4,5-dimethyl-3H-thiazol-(2Z)-ylidene]-amide], Using in Vitro Pharmacological Assays, in Vivo Pain Models, and Pharmacological Magnetic Resonance Imaging

Abstract: Studies demonstrating the antihyperalgesic and antiallodynic effects of cannabinoid CB 2 receptor activation have been largely derived from the use of receptor-selective ligands. Here, we report the identification of A-836339 [2,2,3,3-tetramethyl-cyclopropanecarboxylic acid [3-(2-methoxy-ethyl)-4,5-dimethyl-3H-thiazol-(2Z)-ylidene]-amide], a potent and selective CB 2 agonist as characterized in in vitro pharmacological assays and in in vivo models of pain and central nervous system (CNS) behavior models. In ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
50
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(58 citation statements)
references
References 40 publications
7
50
0
Order By: Relevance
“…administration of the CB2 receptor agonist JWH015 effectively reverses L5 nerve transection-induced behavioral hypersensitivity without antinociceptive tolerance through at least five days of treatment (Romero-Sandoval and Eisenach, 2007). Similar findings have been described with another CB2 receptor agonist, A-836339 (Yao et al, 2009). Taken together, these previous findings suggest that CB1 rather than CB2 receptor agonism is responsible for the antinociceptive tolerance observed in response to CP55940 administration in the current study.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…administration of the CB2 receptor agonist JWH015 effectively reverses L5 nerve transection-induced behavioral hypersensitivity without antinociceptive tolerance through at least five days of treatment (Romero-Sandoval and Eisenach, 2007). Similar findings have been described with another CB2 receptor agonist, A-836339 (Yao et al, 2009). Taken together, these previous findings suggest that CB1 rather than CB2 receptor agonism is responsible for the antinociceptive tolerance observed in response to CP55940 administration in the current study.…”
Section: Discussionsupporting
confidence: 77%
“…Furthermore, sustained spinal or subcutaneous administration of the CB1 receptor agonist, WIN 55,212-2 has been shown to induce hypersensitivity and antinociceptive tolerance in naive mice and rats. In contrast, we (Romero-Sandoval and Eisenach, 2007;Romero-Sandoval et al, 2008a) and others (Yao et al, 2009) have shown that spinal CB2 receptor agonists (such as JWH015) relieve postoperative and neuropathic pain in rodent models without inducing neurological side effects or antinociceptive tolerance. Despite advancements in the molecular mechanisms involved in cannabinoid tolerance (Martini et al, 2010), a better understanding of the respective roles of CB1 and CB2 receptors is required to design effective therapies that do not induce tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…The role of CB2 receptors in modulating peripheral nerves innervating the arthritic joint appear to be complex; close arterial (peripheral) administration of CB2 receptor agonists increased vasodilatation in the inflamed knee joints of rats [75] and facilitated peripheral nerve responses in rats with OA joint damage [52]. Nevertheless, systemic administration of the CB2 receptor agonist A-796260 reversed decreases in grip strength, a surrogate measure of pain, in the monosodium iodoacetate (MIA) model of osteoarthritis pain [76]. Our current lack of knowledge about how arthritis joint pathology impacts on the expression of cannabinoid receptors, both on peripheral nerves and on local cells within the knee joint, hinders the further interpretation of these studies at this point in time.…”
Section: Cb2 Receptor Modulation Of Spinal Immune Cell Functionmentioning
confidence: 99%
“…By contrast, chronic CP55,940, at a dose that produced CB 2 -mediated antiallodynic efficacy, failed to decrease body temperature in CB 1 KO mice, documenting that prolonged activation of CB 2 receptors does not result in hypothermia (Malan et al, 2001;Valenzano et al, 2005;Yao et al, 2009;Elliott et al, 2011;Kinsey et al, 2011;Amenta et al, 2012). Chronic CP55,940-treated WT, but not CB 1 KO mice, showed profound withdrawal signs when challenged with the CB 1 antagonist rimonabant, suggesting precipitation at CB 1 receptors produces withdrawal symptoms (Tsou et al, 1995;Aceto et al, 1996;Cook et al, 1998;Rubino et al, 1998;Lichtman et al, 2001).…”
mentioning
confidence: 99%